Galactic cosmic ray propagation through M dwarf planetary systems. Issue 2 (29th October 2021) - Mesquita, A L; Rodgers-Lee, D; Vidotto, A A; Atri, D; Wood, B E
ABSTRACT: Quantifying the flux of cosmic rays reaching exoplanets around M dwarfs is essential to understand their possible effects on exoplanet habitability. Here, we investigate the propagation of Galactic cosmic rays as they travel through the stellar winds (astrospheres) of five nearby M dwarfs, namely: GJ 15A, GJ 273, GJ 338B, GJ 411, and GJ 887. Our selected stars each have one or two detected exoplanets and they all have wind mass-loss rates constrained by Lyman α observations. Our simulations use a combined 1D magnetohydrodynamic (MHD) Alfvén-wave-driven stellar wind model and 1D cosmic ray transport model. We find that GJ 411 and GJ 887 have Galactic cosmic rays fluxes comparable with Earth's at their habitable zones. On the other hand, GJ 15A, GJ 273, and GJ 338B receive a lower Galactic cosmic ray flux in their habitable zones. All exoplanets in our sample, with exception of GJ 15A c and GJ 411 c, have a significantly lower flux of Galactic cosmic rays than values observed at the Earth because they orbit closer-in. The fluxes found here can be further used for chemical modelling of planetary atmospheres. Finally, we calculate the radiation dose at the surface of the habitable-zone planet GJ 273 b, assuming it has an Earth-like atmosphere. This planet receives up to 209 times less 15 MeV energy cosmic ray fluxes than values observed at Earth. However, for high-energy cosmic rays (∼GeV), the difference in flux is only 2.3 times smaller, which contributes to GJ 273 b receiving a significant surface radiation dose of 0.13 mSv yr −1 (40 per cent of the annual dose on Earth's surface).